"A plus Dans le Bus": Work-Related Stress Among French Bus Drivers. (18th February 2016) - Louit-Martinod, Nathalie; Chanut-Guieu, Cécile; Kornig, Cathel; Méhaut, Philippe
In France, as in many other countries, considerable attention has been paid to health and safety at work and more particularly to the psycho-social risks associated with work. A case study carried out among bus drivers in urban environments in five companies belonging to one of the largest French public transport groups reveals that drivers' health and well-being at work has deteriorated even though the machinery and equipment they use have improved and working time has been reduced. Besides the usual risks to which bus drivers are exposed, new forms of work intensification have emerged, linked to budgetary constraints, urban policies, quality control, geolocation, and verbal and physical assaults. These factors influence working conditions and workloads. This raises the question of the resources deployed by the drivers and/or their representatives. Following Hirschman, various forms of exit are identified, although the new protective rights that have been introduced, which can be likened to a form of voice, do not seem strong enough to reduce the psycho-social risks.